Hours Worked in Europe and the US: New Data, New Answers - Alexander Bick; Bettina Brüggemann; Nicola Fuchs-Schündeln (Institute for the Study of Labor (IZA), 2016)
We use national labor force surveys from 1983 through 2011 to construct hours worked per person on the aggregate level and for different demographic groups for 18 European countries and the US. We find that Europeans work 19% fewer hours than US citizens. Differences in weeks worked and in the educational composition each account for one third to one half of this gap. Lower hours per person than in the US are in addition driven by lower weekly hours worked in Scandinavia and Western Europe, but by lower employment rates in Eastern and Southern Europe.
Keywords: E24; J21; J22; 330; labor supply; employment; hours worked; Europe-US hours gap; demographic structure